2019
DOI: 10.1016/j.addma.2019.02.012
|View full text |Cite
|
Sign up to set email alerts
|

Additive manufacturing of ceramics from preceramic polymers: A versatile stereolithographic approach assisted by thiol-ene click chemistry

Abstract: 2019. Additive manufacturing of ceramics from preceramic polymers: A versatile stereolithographic approach assisted by thiol-ene click chemistry. Additive Manufacturing,27, AbstractHere we introduce a versatile stereolithographic route to produce three different kinds of Si-containing thermosets that yield high performance ceramics upon thermal treatment. Our approach is based on a fast and inexpensive thiol-ene free radical addition that can be applied for different classes of preceramic polymers with carbon… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
99
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 113 publications
(103 citation statements)
references
References 47 publications
3
99
0
1
Order By: Relevance
“…Such a high level of process flexibility enable it can directly fabricate complex internal structures and customized shapes. Up to now, AM has been applied to prepare bone scaffolds from various materials, including metals [12][13][14], polymers [15][16][17] and ceramics [18][19][20], even their composites [21][22][23]. Among them, metal bone scaffolds are most promising for load-bearing bone repair [24].…”
Section: Introductionmentioning
confidence: 99%
“…Such a high level of process flexibility enable it can directly fabricate complex internal structures and customized shapes. Up to now, AM has been applied to prepare bone scaffolds from various materials, including metals [12][13][14], polymers [15][16][17] and ceramics [18][19][20], even their composites [21][22][23]. Among them, metal bone scaffolds are most promising for load-bearing bone repair [24].…”
Section: Introductionmentioning
confidence: 99%
“…For the preparation of metal oxides, several warning is need to unused in rectors' receptacle such as platinum, silica and alumina. Traditionally, a rise -temperature ceramic synthesis, also denoted as ceramic route or bake and shake, is used to fabricate inorganic nanostructures [124][125] . According to process, the materials precursor have intimately been grounded in equipollent amounts and heated at high temperatures for long time to facilitate inter prevalence of the reactant reagents.…”
Section: Ceramic Methodmentioning
confidence: 99%
“…As acrylate monomers, polyethylene glycol diacrylate (PEGDA) [ 31 , 32 ], 1,6-hexanediol diacrylate (HDDA) [ 33 , 34 ], and bisphenol A ethoxylate diacrylate (BEDA) [ 35 , 36 ] were employed; as a photoinitiator, a phosphine oxide-based compound (BAPO) was selected. This photoinitiator is widely employed in SL or DLP 3D printing [ 37 , 38 , 39 ] but it is not considered biocompatible, unlike other photoinitiators such as Lithium phenyl–2,4,6–trimethylbenzoylphosphinate (LAP). However BAPO is 20 times cheaper than LAP and it was demonstrated that it may show low toxicity effects on cells if added in the adequate concentrations [ 30 , 40 , 41 ].…”
Section: Introductionmentioning
confidence: 99%